Upaya Peningkatan Kinerja Sumber Daya Manusia di Rumah Qur'an Raudhatul Qur’an Al-Zahra melalui Pendekatan Manajemen Modern - Irnawiyanti (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze strategies for improving human resource (HR) performance in Rumah Qur'an through the implementation of modern management approaches. A descriptive qualitative design with a case study approach was employed. Participants, including managers, instructors, and support staff at Rumah Qur'an Raudhatul Qur'an Al-Zahra, Murung Raya Regency, were selected using purposive sampling. Data were collected through in-depth interviews, structured observations, and analysis of institutional documents. Thematic analysis was used to identify patterns and relationships in the findings, providing a comprehensive understanding of HR performance enhancement strategies. The results indicated that need-based training, results-oriented performance evaluations, and achievement-based incentives significantly improved HR motivation and productivity. Structured planning, active participation of management in strategic decision-making, and alignment of individual roles with institutional goals further enhanced operational efficiency. These approaches not only fostered a positive work environment but also addressed challenges in maintaining consistent performance levels.This research concludes that implementing modern management practices effectively supports HR performance improvements in religious educational institutions. Sustainable management systems and the integration of technology into institutional processes are recommended for long-term success. These strategies are particularly relevant in addressing the unique operational dynamics of Rumah Qur'an, contributing to its mission of delivering quality religious education. This study highlights the importance of aligning HR strategies with organizational objectives to achieve optimal outcomes and sets a foundation for future research on HR management in similar contexts.